2020
DOI: 10.1111/aor.13778
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular events in children on intracorporeal continuous‐flow left ventricular assist devices

Abstract: Continuous-flow intracorporeal left ventricular assist devices (CF-LVAD) are used more frequently in the pediatric population. One of the major complications of CF-LVAD is cerebrovascular events (CVEs). Limited information is available on this complication in pediatric patients. We hereby present our experience on CVEs in children under CF-LVAD support in our institution. A retrospective, single center review of 21 patients younger than 19 years of age who underwent CF-LVAD implantation between June 2014 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Finally, pump thrombosis can lead to morbidity in the form of stroke. One study found that 50% of patients who suffered from an ischemic or hemorrhagic stroke had been treated for pump thrombosis previously (29). This finding was also noted in another study of stroke rates in CF-VADs, with 75% of patients suffering a CVA having been previously treated for pump thrombosis (10).…”
Section: Pump Thrombosis/pump Exchangementioning
confidence: 78%
See 1 more Smart Citation
“…Finally, pump thrombosis can lead to morbidity in the form of stroke. One study found that 50% of patients who suffered from an ischemic or hemorrhagic stroke had been treated for pump thrombosis previously (29). This finding was also noted in another study of stroke rates in CF-VADs, with 75% of patients suffering a CVA having been previously treated for pump thrombosis (10).…”
Section: Pump Thrombosis/pump Exchangementioning
confidence: 78%
“…CVAs are one of the most significant complications following long-term CF-VAD implant, with the majority of events occurring early after implant (29). Single center analyses have shown that CVA rates vary between centers.…”
Section: Cerebrovascular Accident (Cva)mentioning
confidence: 99%
“…Some of our included studies seem to reflect this too. For example, some studies with older patients show lower recovery rates [ 15 , 16 , 21 , 25 ], whereas others with younger children show higher recovery rates [ 22 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HeartWare HVAD was removed from the market in June 2021, due to an the rates of thromboembolic stroke seen in adult patients supported with the device. Although this was not evident in pediatric patients, the device is no longer available for any population [ 49 ]. As a result, the choice of implantable devices for even larger children and teenagers is again somewhat limited.…”
Section: Durable Ventricular Assist Devicesmentioning
confidence: 99%